Membangun Generasi Qur'ani: Panduan Pemilihan Pendidikan Anak Menurut Al-Qur'an - Fatoni, Imam (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2025)
Children's education is a crucial aspect in shaping the character and future of a nation. In the Islamic context, the Qur'an provides very clear guidelines on how to educate children, emphasising the balance between scientific and moral education. This research aims to explore and analyse the concept of choosing children's education in the Qur'anic perspective, as well as its relevance in facing the challenges of education in modern times. The type of research used is qualitative with a literature study approach. The main data sources of this research are Qur'anic verses related to child education, interpretations of great scholars, and related scientific literature. The purpose of this study is to understand the guidelines of child education according to the Qur'an and provide insight into how to apply them in the context of child education in the era of globalisation. The results show that the Qur'ān emphasises two main aspects of child education: the formation of noble morals and the development of knowledge. The verses in Surah Luqman and Surah Al-Alaq show the importance of the role of parents in educating children according to religious values, as well as encouraging the pursuit of knowledge that is useful for life. This study also found challenges in implementing Qur'an-based education in modern times, which are influenced by technological developments and globalisation.